Mild Fractionation of Hydrophilic and Hydrophobic Components From Neochloris oleoabundans Using Ionic Liquids - Desai, Rupali K.; Fernandez, Maria Salvador; Wijffels, Rene H.; Eppink, Michel H. M. (Frontiers in Bioengineering and Biotechnology, 2019)
Microalgae are a promising source for proteins, lipids and carbohydrates for the food/feed and biofuel industry. To make microalgae production economically feasible it is necessary to optimally use all produced compounds keeping full functionality. Therefore, biorefining of microalgae is the key to lower the cost of algal products using mild and effective processing techniques. In this article we have tested the feasibility of aqueous solutions of imidazolium and phosponium ionic liquids to selectively milk the hydrophobic lipids from N. oleoabundans biomass out of intact cells and recover after cell disruption the hydrophilic fraction containing proteins and carbohydrates. The results showed that the ionic liquid Tributylmethylphosphonium methyl sulfate (TBP SO4; Cyphos 108) is able to permeabilise fresh intact cells of N. oleoabundans for extracting 68% of total lipids out of the cells, whereas, after cell disruption 80% of total proteins and 77% of total carbohydrates could be obtained in aqueous buffers. This concept kept the recovered proteins in their native form without interacting with the ionic liquids that will denature the proteins. Selective biorefinery of different components from microalgae using ionic liquid-TBP SO4 explains the novelty of this concept.